Effect of non-surgical therapy on periodontal clinical parameters in patients using cannabis - Gómez-Osorio, Natalia (2021)
The objective was to analyze the effects of non-surgical periodontal therapy on clinical parameters in patients using cannabis. A non-randomized clinical study was conducted with 40 volunteers from Universidad de Antioquia divided into 2 groups: 20 participants using cannabis (smokers) and 20 non-users (control). All clinical parameters regarding probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP) were recorded at baseline and 3 months after non-surgical periodontal therapy. Differences between groups were assessed with the Mann Whitney test and were considered significant when p≤0.05. Data was analyzed using the SPSS statistical software. Participants using cannabis had a frequency of use of 3 times/day (60%), 2 times/day (10%) and 1 time/day (30%). In general, smokers had higher BOP at both examinations as opposed to non-smokers, this difference being statistically significant (p<0.05). No differences were observed for PD with a mean of 2.09 ± 0.73 mm at baseline and 2.15 ± 0.65 mm at 3 months, showing a small increase between the two. CAL was also slightly higher in smokers than in non-users. There was no significant evidence in the studied population relating periodontal disease with cannabis consumption. The response of periodontal tissues to non-surgical therapy was similar between cannabis users and non-users.